Biofortification - A Sustainable Agricultural Strategy for Reducing Micronutrient Malnutrition in the Global South - Bouis, Howarth E.; Welch, Ross M. (Wiley, 2010)
Minerals and vitamins in food staples eaten widely by the poor may be increased either through conventional plant breeding or through use of transgenic techniques, a process known as biofortification HarvestPlus seeks to develop and distribute cultivars of food staples (rice [Oryza sativa L.], wheat [Triticum aestivum L.], maize [Zea mays L.], cassava [Manihot esculenta Crantz], pearl millet [Pennisetum americanum Leeke], beans [Phaseolus vulgaris L.], sweet potato [Ipomoea batatas L.]) that are high in Fe, Zn, and provitamin A through an interdisciplinary global alliance of scientific institutions and implementing agencies in developing and developed countries. Biofortified crops offer a rural‐based intervention that, by design, initially reaches these more remote populations, which comprise a majority of the undernourished in many countries, and then penetrates to urban populations as production surpluses are marketed. Thus, biofortification complements fortification and supplementation programs, which work best in centralized urban areas and then reach into rural areas with good infrastructure. Initial investments in agricultural research at a central location can generate high recurrent benefits at low cost as adapted biofortified cultivars become widely available in countries across time at low recurrent costs. Overall, three things must happen for biofortification to be successful. First, the breeding must be successful—high nutrient density must be combined with high yields and high profitability. Second, efficacy must be demonstrated—the micronutrient status of human subjects must be shown to improve when consuming the biofortified cultivars as normally eaten. Third, the biofortified crops must be adopted by farmers and consumed by those suffering from micronutrient malnutrition in significant numbers.